Septic arthritis of the hip in a Cambodian child caused by multidrug-resistant Salmonella entericaserovar Typhi with intermediate susceptibility to ciprofloxacin treated with ceftriaxone and azithromycin - J. M. Pocock (2018)
Septic arthritis is a rare complication of typhoid fever. A 12-year-old boy without pre-existing disease attended a paediatric hospital in Cambodia with fever and left hip pain. A hip synovial fluid aspirate grew multidrug-resistant Salmonella enterica ser. Typhi with intermediate susceptibility to ciprofloxacin. Arthrotomy, 2 weeks of intravenous ceftriaxone and 4 weeks of oral azithromycin led to resolution of symptoms. The optimum management of septic arthritis in drug-resistant typhoid is undefined. © W. S. Maney & Son Ltd 2014.